2021
DOI: 10.3389/fmicb.2020.620843
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Virulence and Genomic Analysis of Streptococcus suis Isolates

Abstract: Streptococcus suis is a zoonotic bacterial swine pathogen causing substantial economic and health burdens to the pork industry. Mechanisms used by S. suis to colonize and cause disease remain unknown and vaccines and/or intervention strategies currently do not exist. Studies addressing virulence mechanisms used by S. suis have been complicated because different isolates can cause a spectrum of disease outcomes ranging from lethal systemic disease to asymptomatic carriage. The objectives of this study were to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 86 publications
5
20
0
Order By: Relevance
“…There was a high rate of carriage of AMR genes in S. suis isolates in this study, and similar to previous S. suis genotypic AMR studies globally ( 20 , 22 , 23 ), most of the isolates carried genes associated with resistance to tetracycline, lincosamides, and macrolides. Consistent with those studies, tet(O) was the most prevalent tetracycline resistance gene detected in the S. suis isolates.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…There was a high rate of carriage of AMR genes in S. suis isolates in this study, and similar to previous S. suis genotypic AMR studies globally ( 20 , 22 , 23 ), most of the isolates carried genes associated with resistance to tetracycline, lincosamides, and macrolides. Consistent with those studies, tet(O) was the most prevalent tetracycline resistance gene detected in the S. suis isolates.…”
Section: Discussionsupporting
confidence: 90%
“…The recent increase in the prevalence of disease caused by serotype 9 isolates globally requires more attention to understanding the pathogenesis mechanisms that may be unique to each serotype. There was a high rate of carriage of AMR genes in S. suis isolates in this study, and similar to previous S. suis genotypic AMR studies globally (20,22,23), most of the isolates carried genes associated with resistance to tetracycline, lincosamides, and macrolides. Consistent with those studies, tet(O) was the most prevalent tetracycline resistance gene detected in the S. suis isolates.…”
Section: Multidrug Resistancessupporting
confidence: 90%
See 1 more Smart Citation
“…The tetracycline-resistance gene, tet M, encoded TetM protein responsible for the inhibitory effect of tetracycline, is distributed among virulent S. suis. [ 34 , 35 , 36 ]. An outbreak report in China demonstrated that the tetracycline-resistance strains were associated with S. suis infections in both pigs and humans [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among 29 serotypes, WGS has been applied to the serotype 2 strains worldwide for, as examples, characterization of outbreaks, evaluation of S. suis reinfection, determining the population structure of S. suis strains, and identifying pathotypes or virulence traits ( Estrada et al, 2019 ; Hatrongjit et al, 2020 ). Several studies have also been conducted on serotypes other than serotype 2 including serotypes 3–9, 14, 16, 19, 20, 21, 22, 26, and unencapsulated strains, although most of them were of swine origin ( Hu et al, 2011 ; Wang et al, 2013a , b , 2014 ; Baig et al, 2015 ; Yoshida et al, 2017 ; Zheng et al, 2018 ; Niemann et al, 2019 ; Stevens et al, 2019 ; Bunk et al, 2021 ; Liang et al, 2021 ; Nicholson et al, 2021 ). To date, there has been no WGS performed on S. suis serotype 24 strains recovered from humans.…”
Section: Introductionmentioning
confidence: 99%